Conselhos Tutelares E Articulação Política - Angulo, Kathleen Ferreira [UNIFESP] (2017)
The creation of the Child Care Councils in Brazil was established in 1990 along with the Child and Adolescent Statute (ECA). Capturing the promises of redemocratization, social participation and the demand for rights, the Councils were thought and designed as community bodies with representatives elected from time to time, being responsible for assignments ranging from the care of children and adolescents violated in their rights to the search for the prevention of violation, such as advising the local government in the development of the budget proposal for plans and programs related to the rights of children and adolescents. The literature on the subject is produced within several areas of knowledge - with a predominance of the health area - and little worked by the Social Sciences, especially regarding the relation of the Child Care Councils with the public policies. In general, the researches highlight the importance of this instrument for guaranteeing the rights of children and youth, but note that: i. the Child Care Councils do not have adequate infrastructure for the execution of the work, whether it is related to the places of care or related to the poor formation of the counselors and their low remuneration; ii. the Child Care Councils do not have their role understood neither by society nor by the public sector, which creates a series of constraints and difficulties to the daily work; iii. the Child Care Councils have distanced themselves from the ECA proposal, since they still reproduce the "minorist" ideology and have approached the Judiciary to the detriment of the rapprochement with local communities and social movements. In order to understand the role of the Child Care Councils in the elaboration of public policies and the factors for a Council to act for this purpose, this study studied five Child Care Councils of the city of Guarulhos (SP) during the year 2017. The results point that, given the fragility of the relationship with the channels of the municipal service network, the lack of training that the counselors receive, and the poor regulation of public policy for children and adolescents, counselors carry out their work by mobilizing their personal repertoires, giving space to a unadjusted and with a high degree of discretion. To reach the results, the research was based on semi-structured interviews, which made possible the analysis of the social networks (ARS) of the counselors.